Exosomal biomarkers and immune checkpoint inhibitors: advancements and future prospects - Can Lu; Muhammad Tufail; Can-Hua Jiang; Ning Li (Cancer Cell International)
Abstract This review examines the growing role of exosomes and circulating exosomal biomarkers in predicting response to immune checkpoint inhibitors (ICIs) in cancer therapy. While ICIs have revolutionized cancer treatment, predicting patient response remains a major challenge. Exosomes, small extracellular vesicles involved in intercellular communication, have emerged as potential biomarkers for monitoring and enhancing ICI efficacy. However, significant knowledge gaps exist in understanding how exosomal cargo, particularly its molecular composition and immune-modulatory functions, can influence treatment outcomes. The review explores the mechanisms of action of ICIs, focusing on immune checkpoint blockade and the tumor microenvironment (TME) impact on immune responses. We also discuss the potential of exosomal biomarkers to serve as reliable indicators of immunotherapy response, highlighting their ability to reflect dynamic changes in the tumor and immune system. Despite their promising potential, challenges remain in translating exosomal biomarkers into clinical practice, including issues related to standardization and sensitivity. The review concludes by addressing these challenges and offering future perspectives on how exosomal biomarkers could shape the future of cancer immunotherapy, providing critical insights for personalized treatment strategies.